2016
DOI: 10.1080/09602011.2016.1257435
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the minds of others: A review of social cognition treatments and their relevance to traumatic brain injury

Abstract: Social cognition is widely regarded as an essential skill with which to understand the social world. Despite this, the role that social cognition plays in outcome, and whether deficits are remediable after traumatic brain injury (TBI), are not yet well known. The current review examines the construct of social cognition and presents a conceptual biopsychosocial model with which to understand the social cognitive process. This is related to the literature on social cognitive deficits in TBI and we discuss relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 220 publications
(267 reference statements)
1
72
0
2
Order By: Relevance
“…Differences generally are small (e.g., accounting for <10% of variance in scores) and are mostly for threat-related affective displays. Analysis of 14,000 samples of written and spoken language showed that women also used more emotion words (e.g., happy, certainty, nervous, and hate) than men, and fewer swear words (31), although again effect sizes were small [i.e., [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Sex Differences In Social Cognition In Typical Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences generally are small (e.g., accounting for <10% of variance in scores) and are mostly for threat-related affective displays. Analysis of 14,000 samples of written and spoken language showed that women also used more emotion words (e.g., happy, certainty, nervous, and hate) than men, and fewer swear words (31), although again effect sizes were small [i.e., [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Sex Differences In Social Cognition In Typical Adultsmentioning
confidence: 99%
“…The review focuses on two aspects of social cognition that have been studied in TBI: recognition of emotions from facial affect; and Theory of Mind (ToM), the ability to attribute mental states to oneself and others, and use that information to make predictions about others' actions (9). We chose these two aspects of social cognition because they have been linked to broader social outcomes like quality of life and social reintegration, both conceptually (10)(11)(12), and empirically (13)(14)(15)(16)(17)(18)(19)(20). We consider data from typical adults and adults with TBI, in the broader context of common stereotypes about social skills and behaviors in men vs. women.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the associations between physiological variables including heart rate changes and the likelihood of response will yield insights relevant to the development and implementation of targeted treatment approaches to autonomic deficits in adults after a brain injury. Whilst there is now enough evidence to support routine clinical assessment of social cognition (though there is evidence to suggest this is not happening [62]), more research is needed to establish evidence for social skills interventions in this field [63].…”
Section: Discussionmentioning
confidence: 97%
“…A more recent review of social cognition treatments and TBI (Cassel et al . ) highlights the paucity of interventions for social cognition, and summarizes that those that do exist primarily use stimuli consisting of pictures, videos and role‐play. The authors suggest that social cognition interventions for other populations may be used to inform treatments for people with TBI, and more naturalistic and experiential interventions could transfer better to real‐life contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Ylvisaker et al (2005) summarized research findings about behavioural and social interaction interventions for people with TBI and suggested that interventions should focus on situational training; that is, practicing the skill in the situation that requires it, and cautioned against social skills groups that may train discrete skills out of context. A more recent review of social cognition treatments and TBI (Cassel et al 2016) highlights the paucity of interventions for social cognition, and summarizes that those that do exist primarily use stimuli consisting of pictures, videos and role-play. The authors suggest that social cognition interventions for other populations may be used to inform treatments for people with TBI, and more naturalistic and experiential interventions could transfer better to real-life contexts.…”
Section: Discussionmentioning
confidence: 99%